Solution:
We know that:
- Interior angles of a triangle sum up to 180°.
- [tex]3a + 7u + 9 = 180\°[/tex]
This means that:
- [tex](7u + 9) + (2a - 3) + 32 = 3a + 7u + 9[/tex]
Let's simplify the equation to find a.
Step-by step calculations:
Open the brackets:
- [tex](7u + 9) + (2a - 3) + 32 = 3a + 7u + 9[/tex]
- [tex]7u + 9 + 2a - 3 + 32 = 3a + 7u + 9[/tex]
Cancel same terms on both sides:
- [tex]7u + 9 + 2a - 3 + 32 = 3a + 7u + 9[/tex]
- [tex]2a - 3 + 32 = 3a[/tex]
Simplify the LHS:
Subtract 2a both sides:
- [tex]2a - 2a + 29 = 3a - 2a[/tex]
- => [tex]29 = 3a - 2a[/tex]
Simplify the RHS and change the sides:
- => [tex]\bold{a = 29}[/tex]
Let's substitute the value of a in 3a + 7u + 9 = 180° to find u.
- [tex]3a + 7u + 9 = 180\°[/tex]
- => [tex]3(29) + 7u + 9 = 180\°[/tex]
Simplify the LHS:
- => [tex]87 + 9 + 7u = 180[/tex]
- => [tex]96 + 7u = 180[/tex]
Subtract 96 both sides:
- => [tex]96 - 96 + 7u = 180 - 96[/tex]
- => [tex]7u = 84[/tex]
Divide 7 both sides:
- => [tex]\frac{7u}{7} = \frac{84}{7}[/tex]
- => [tex]\bold{u = 12}[/tex]